Interpretation of the Behavior of Pile Foundations in Unsaturated Soils Subjected to Axial and Lateral Loading - Cheng, Xinting (Université d'Ottawa / University of Ottawa, 2023)
Many regions in the world are experiencing drying trends due to climate change effects. The cumulative influence of environmental activities associated with rainfall infiltration, evaporation and plant transpiration contributes to a groundwater table (GWT) typically located at a great depth, especially in arid and semi-arid regions. Due to this reason, natural soils are widely found to be in a state of unsaturated condition. Unsaturated soils are tri-phase materials comprised of solids (i.e., soil particles), liquid (i.e., water) and gas (i.e., air), which have more complex hydraulic and mechanical properties in comparison to saturated soils. Pile foundations are widely used to transfer large loads from the superstructure to a deeper stratum with reduced soil settlements. In many scenarios, pile foundations are either entirely or partly embedded in unsaturated soils. For the rational design of pile foundations, it is important to ensure that it can support different types of loads that include axial, lateral or transversal loads arising from the super structures that are safely transmitted to the soil below without undergoing bearing capacity failure in addition to limiting the excessive deformation. However, the load transfer mechanism of piles embedded in unsaturated soils has not been fully investigated in the presently available literature. Unreliable estimations are likely if saturated soil mechanics principles are used to design or analyze the nonlinear response of pile foundations. Therefore, a better understanding of the mechanical properties of unsaturated soils and pile-soil interaction is required for the rational interpretation of the load-displacement behavior of piles in unsaturated soils. The focus of this thesis has been directed towards investigating the influence of varying unsaturated conditions on the behavior of piles under axial and lateral loadings extending the mechanics of unsaturated soils. To investigate the behavior of laterally loaded piles in unsaturated soils, a nonlinear analytical method is proposed to predict the lateral response of rigid piles considering the influence of matric suction. The lateral load corresponding to lateral displacement is derived considering three different states. Good comparisons are achieved between the results of the analytical method and measurements from eight published field pile load tests in unsaturated soils. Finite element analyses are then undertaken to model the lateral response of pile foundations. The proposed numerical method is validated against two experimental studies from the literature. To investigate the behavior of axially loaded piles, an analytical approach is proposed for predicting the end-bearing capacity of driven piles that are subjected to axial loads based on the stress characteristic method. The validation of the analytical method is established using eleven case studies of driven piles in saturated soils and two in unsaturated soils. Numerical analysis is undertaken to simulate a published model test of driven piles in unsaturated sand. Both dynamic and static analysis are involved in the numerical analysis to simulate the pile driving and the following pile loading. A simplified methodology is first proposed for estimating the load-displacement response of single piles under axial loading using modified hyperbolic function-based load transfer models. Then the proposed model is extended for pile groups considering the interaction effects between individual piles. The validity of the approach for both single pile and pile groups is demonstrated using three pile load tests results from the literature. Furthermore, a three-dimensional (3D) numerical analysis is undertaken to analyze the nonlinear response of pile groups implementing a user-defined subroutine into ABAQUS software. Good comparisons are found between the predictions from both the proposed analytical method and numerical analysis with the measurements. In addition, a comprehensive numerical technique is proposed for simulating the load-displacement behavior of single piles embedded in unsaturated soils using finite element analysis. A user-defined subroutine is implemented into ABAQUS taking account of nonlinear shear strength and modulus of elasticity of unsaturated soils with respect to matric suction. The numerical analyses are then performed on four pile load tests that include two model pile tests in the laboratory and the remainder two from the field tests that were gathered from the published literature. Reasonably good predictions are achieved for all cases. The proposed numerical technique is a simple and useful tool for use in geotechnical engineering practice for the rational design of pile foundations in unsaturated soils. The bearing capacity and settlement are two key properties of pile behavior, which should be estimated rigorously considering the influence of matric suction. The studies summarized in this thesis provide valuable insight towards implementing the unsaturated soil mechanics into the rigorous design of pile foundations in unsaturated soils considering the influence of matric suction under axial and lateral loading. The proposed analytical and numerical models are useful for the rational design of pile foundations for both saturated and unsaturated soil conditions.
Keywords: Unsaturated soils; Pile foundation; Axially loaded pile; Matric suction